Fear, Trust and Demand for Regulation: Evidence from the Covid-19 Pandemic in Russia - Ekaterina Borisova; Timothy Frye; Koen Schoors; Vladimir Zabolotskiy (Center for Economic Studies and ifo Institute (CESifo), 2022)
Understanding demand for state regulation is a foundational issue for social science. To account for this demand, existing theories rooted in market failure and government failure have focused on various forms of trust, but have paid little attention to fear. We test how fear and trust shape demand for government regulation by drawing on especially precise measures of Covid-related regulations gathered in a survey of more than 23,000 respondents in 61 Russian regions. We show that fear of contracting the virus is directly related to greater demand for regulation. In addition, the impact of trust is conditional on the level of fear. Higher interpersonal trust is related to lower demand for Covid-19 regulation, while higher institutional trust is associated with greater demand, but, provided fear is sufficiently great, demand for regulation will be high regardless of levels of interpersonal and institutional trust. These results inform debates about theories of regulation, identify critical scope conditions for existing research on trust and demand for regulation, and open a fruitful line of research by examining how fear of social bads shapes support for state intervention.
Keywords: D64; H11; I12; Z13; 330; fear; trust; demand for regulation; Covid-19; Russia